Technology-mediated education for marginalized populations: financial literacy gap - Jaya, Asri (CV. Bimbingan Belajar Assyfa, 2023)
A person's financial attitude includes thoughts, attitudes, and self-confidence in managing money. A positive financial attitude is essential for responsible financial behavior and long-term well-being. Financial literacy includes financial behavior and consequences, not just information and skills. Technology in financial education has the potential to reduce the picture of financial literacy in developing countries. This research explains how technology-mediated financial education can be flexible, cost-effective, and adaptable, and reach communities underserved by financial services. This research also identified barriers such as inadequate infrastructure, limited access, and language and cultural barriers. Through extensive literature insights from various sources such as